Does Increased Fructose Consumption Increase Atherosclerosis Burden in Patients with NSTEMI? - Uğur Küçük; Bihter Taşdelen; Kudret Pesenli (International Journal of the Cardiovascular Academy, 2024)

(untitled)
Background and Aim: The pathophysiological process of coronary artery disease is not completely understood. According to some studies, fructose consumption is associated with coronary artery diameter change and blood flow; however, the relationship between fructose consumption and coronary atherosclerotic burden has not been adequately studied, and the purpose of our study was to investigate this relationship. Materials and Methods: One hundred and fifty patients with non-ST-elevation myocardial infarction (NSTEMI) who underwent coronary angiography were divided into two groups: low (<23) and high (≥23) synergy between percutaneous coronary intervention with taxus and cardiac surgery (SYNTAX) scores. Fructose consumption was calculated for both groups, and the calculated fructose consumption was compared between the groups. Results: Fructose consumption was higher in patients with a high SYNTAX score than in those with a low SYNTAX score (10.75 ± 2.04 and 6.86 ± 1.54, P < 0.001). Receiver operating characteristic curve analysis showed that the cut-off value of fructose consumption was 41.50 (g) for the prediction of high SYNTAX score (area under the curve: 0.891, sensitivity: 94%, specificity: 73%, P < 0.001). Fructose consumption was determined to be a predictor of high SYNTAX score in patients with NSTEMI (odds ratio: 1,239; 95% confidence interval: 1,146-1,339; P < 0.001). Conclusion: Patients with high SYNTAX scores consumed a higher amount of fructose than those with low SYNTAX scores. High intake of fructose may play a role in coronary atherosclerotic burden score in patients with NSTEMI.